Variation of food web structure in macrobenthic communities in low diversity system as determined by stable isotope-based community-wide metrics. (5th September 2022) - Ziółkowska, Marcelina; Sokołowski, Adam
Abstract: Recognition of spatial and temporal variations of food webs is of fundamental importance for understanding ecological processes and biodiversity management. Changes in trophic organization alter routing patterns and dynamics of energy fluxes among ecosystem compartments and ultimately affect the ecosystem functioning. In this study, stable isotopes of carbon and nitrogen (δ 13 C and δ 15 N) were employed to define trophic niche and diversity as well as redundancy of four macrofaunal benthic communities in a low diversity, brackish system of the Puck Lagoon (southern Baltic Sea). The Bayesian mixing models were used to delineate community-wide metrics at different trophic levels. Benthic macrovegetation appeared to facilitate directly and indirectly development of different trophic niches for consumers by diversification of basic carbon resources and providing habitat structure. In habitat with dense vegetation, diverse food sources supported benthic fauna of different feeding modes. Communities from sandy bottom with low biomass of macrophytes showed compact food webs of lower trophic diversity. Reliance on one dominant resource (suspended particulate organic matter-SPOM, and phytoplankton) resulted here in simplification of food web structure with a large proportion of species with one feeding mode (suspension feeders). Widening of δ 13 C range (CR) and δ 15 N range (NR) in the cold season was related to the extended carbon isotope ratios of organic matter sources and the presence of omnivorous and carnivorous fish that migrated towards the shoreline. A decreased trophic diversity during a vegetative season (spring-summer) was attributed to a narrowed isotopic range of primary producers that incorporated isotopically similar biogenic substances. Geographical and seasonal differences of trophic structure highlighted important natural variation of benthic communities which can benefit ecological restoration programmes and biodiversity management of coastal and marine areas. Highlights: Variations of community trophic niche of benthic faunal communities in space and time were defined in a low diversity system. Sandy bottom habitats hosted compact communities of simple food web structure that relies one dominant food source. Dense vegetation supported higher trophic diversity and more complex food webs. Seasonal variations of trophic diversity of the faunal communities were driven primarily by the heterogeneity and isotopic composition of the resources. Trophic niches of communities were temporally enlarged by the appearance of migrant species that show diversified food preferences.